Virus strahu: nacionalizem in pandemična družba - Bajt, Veronika (Monitor ISH, 2021)
Research confirms a global rise of nationalism (Bieber 2020), racism (Chan and Montt Strabucchi 2020) and hate speech in connection with the outbreak of covid-19 (Moreno Barraneche 2020). External enemies or dangerous Others are far from concepts associated only with history, as they also describe strategies for dealing with challenges of modernity. The paper analyzes governmental measures taken in Slovenia in the period since the outbreak of the coronavirus that refer to border crossing, comparing them with historical examples of addressing infectious diseases by quarantine and border closure. The analysis shows a rise in exclusionary nationalism that mostly affects already marginalized social groups, especially the migrant population, i. e. third country nationals.
Keywords: Covid-19; Izseljevanje in priseljevanje; Karantena; migracije; Nacionalizem; pandemije; zaščitni ukrepi